PENGARUH SIKAP INOVATIF DAN KEDISIPLINAN TERHADAP KOMPETENSI GURU SD NEGERI GUGUS SEKOLAH 1, KECAMATAN KARANGPLOSO, KABUPATEN MALANG - Ari Alfianah (PROGRAM PASCA SARJANA MAGISTER MANAJEMEN INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2021)
This study aims to determine the effect of: 1) Innovative attitude towards teacher competence; 2) Discipline towards teacher competence; 3) Innovative attitude and discipline towards teacher competence of SD Negeri 1 Cluster School, Karangploso District, Malang Regency. A total of 77 elementary school teachers in School Cluster 1, Karangploso District, Malang Regency. The results of this study indicate, among others: 1) Innovative Attitudes have a significant effect on Teacher Competence; 2) Discipline has a significant effect on Teacher Competence; 3) Innovative and Disciplined Attitudes have a significant effect on the Competence of Elementary School Teachers in Cluster 1, Karangploso District, Malang Regency.